Analysis for Hydrological Regime of the Lower Reaches of Geheyan Reservoir Based on IHA-RVA Method - TU Yulyu; LI Yinghai; GUO Jiali; NIE Panpan (Renmin Zhujiang)
In order to evaluate quantitatively the change of ecological and hydrological regime of the lower reaches of Geheyan reservoir,based on the daily flow data of Changyang hydrological station from 1951 to 2010,this paper analyzes the flow trend with the non-parameter Mann-Kendall trend test,and the abrupt change points by Mann-Kendall test,moving t test and ordered clustering,and then comprehensively evaluates the ecological and hydrological changes of Changyang section at the lower reaches of the Geheyan reservoir with IHA-RVA (indicators of hydrologic alteration and range of variability approach) and hydrological alteration degree evaluation.The results show that:The annual average runoff of Changyang station shows unobvious downward trend.In 2000,there was an abrupt change.In overall,the hydrological regime is featured with 58% of moderate change,and indicators with the most obvious change are the base flow index,time of annual minimum flow,duration of low flow pulse and number of reversals,which can provide reference for water ecological protection of Qingjiang River Basin.